ANALISIS UANG MUKA DALAM AKAD MURABAHAH PADA KREDIT PEMILIKAN RUMAH (Studi Pada BNI Syariah KCP JABABEKA Cikarang Bekasi) - Ahmad, Listian; Sulistiana, Tri (DPPM Universitas Pelita Bangsa, 2021)
According to the Classical Islamic Literatures, down payment is clearly known as Urban in Arabic, or in Bahasa accepted by Panjar, which means an initial agreed contract into a transaction. Islamic Scholars arguably have different opinions in implementing down payment as a method in the transaction. There are some scholars who do not agree to put down payment as a particular way in the transaction, but others do. However, by exercising the quality of specific reasoning that is applied, and also the fact of the acceptance of the system of transaction, therefore this method of payment is generally accepted. The first objective of this study is to determine the down payment mechanism and implementation of KPR financing with a murabahah contract at BNI Syariah KCP JABABEKA Cikarang Bekasi which is contained in the Griya iB Hasanah product. Second, to find out the settlement steps in case of problematic or bad financing. The three views of Islamic law in the perspective of muamalah fiqh towards down payments in a murabahah contract on a KPR at BNI Syariah KCP JABABEKA Cikarang Bekasi. This type of research is qualitative research. The data used are primary and secondary data. Primary and secondary data were obtained from observations, interviews, documentation, field studies, and from existing literature. The results of this study are advances in murabahah contracts on KPR in BNI Syariah which refer to the DSN-MUI Fatwa Number 13 of 2000 concerning advances in murabahah. It seems that the fatwa is influenced by the thoughts / opinions of Imam Ahmad and his followers who allow buying and selling transactions using advances, then referring to the existing regulations of the OJK, the regulator of BI, that every financing, both conventional and sharia, must have an advance.